ISOLASI DAN KARAKTERISASI HEVEIN DARI LATEKS HEVEA BRASILENSIS KLON GT. I DAN LCB - Ukun MS Soedjanaatmadja, R.
Indonesia is one of the biggest rubber producer, next to Malaysia. Considering the produce of natural rubber, the culture of the rubber plant, Hevea brasiiiensis, is economically most important to tropical countries that produce rubber. And the knowledge of molecular biology of Hevea latex is most important in increasing latex production. Fundamental research of this biological material are certainly most interesting. Latex of Hevea brasiiiensis is a milky Juice or a cell liquid in the form of suspension, containing rubber and non-rubber particles, such as protein, carbohydrate, lipids. karotenoid and others. The presence of specific protein in the latex, which is supposed to have a very great influence on the latex flow, has attracted researchers to investigate the function or the role of that protein. One of the protein compounds found in the bottom fraction of latex, the Hevein, has been isolated and purifiedby means of Fresh latex centrifugation, freezing-melting process, precipitation using ammonium sulphate salt with a saturation variety of 0-65 X and 65-100X, fractionation with gel filtration of sephadex G-25,fractionation with CMC column and followed by dialysis and electrodialysis processes. As a result, Hevein crystal has been obtained, which, in the process of agar-electrophoresis (under veronal buffer of pH 8,6; 0,05 M) has been observed to have moved towards the positive pole. Hevein characterization has been carried out by means of disc-gel poliaerylamide electrophoresis, SOS-gel polyacryl - amide electrophoresis and agar-gel electrophoresis. From this characterization the result has been obtained, showing that the isolated Herein posseses very high purity, with the molecular weight of 5700 (clone GT.I) and 6600 (clone LCB). And from the Hevein obtained, it has been found that Hevea latex clone GT.l possesses greater Hevein contents then that of LCB.